Comparative Study of Intercity Transport Companies In Benin City, Nigeria (Journal of Entrepreneurship and Business, 2022)
This study examined comparative study of intercity transport companies in Benin City, Nigeria. The study sample consists of four hundred respondents drawn from across the four leading interstate transport companies in Benin City. A questionnaire instrument was used to gather the needed information and the analytical techniques employed include simple percentage, t-test and Analysis of variance (ANOVA). All tests were performed at the 0.05 level of statistical significance. The findings revealed that God is Good Motors was rated far higher than the other transport companies by passengers while Iyare Motors was rated the least. Furthermore, we found that there is no significant relationship between respondents’ gender and customer perception of service quality in interstate transport companies. However, educational qualification and age had a significant relationship with passengers’ perception of service quality. We recommend that interstate transport companies should concentrate more on issues such as safety, comfort on the road, respect for passengers and regular maintenance of vehicles as well as replacing unserviceable vehicles with new ones to avoid frequent vehicle breakdown on the high way